New opportunities for increasing the renovation rate of buildings - Dipl. – Ing. Manfred Sonnleithner, MSc (Slovak University of Technology, Faculty of Architecture and Design, 2021)
The paper focuses on the long-standing problem of too low renovation rates of existing buildings and on practice-oriented solutions. The European Commission has set the goal of at least doubling the renovation quota with “The European Green Deal” and published the “Strategy for a Renovation Wave for Europe - greening our buildings, creating jobs, improving lives” on 14 October 2020. As in previous years, technical specifications have been defined even more strictly and limit values for energy consumption have been further reduced with the aim to reduce CO2 emissions. The high quality of the renovation measures is ensured within the European Union and its member states. However, this has not yet been the case in relation to the quantity of implemented renovation projects. The thesis investigates which factors were neglected or were not taken into consideration sufficiently in the past, and, because of that, countries like Austria could not achieve their goals with regard to the renovation rates. This is done by identifying, selecting and verifying both specific and potential conflicting goals. On the basis of the description and analysis of the background to these potential conflicts, the actual obstacles are identified and approaches to their solutions are defined. The formulated approaches should form the basis for future in-depth discussion and further development of specific detailed solutions. The implementation of these results in a comprehensive package with technical regulations such as the “Renovation Wave for Europe” and “The European Green Deal”, opens up new opportunities for achieving the set goals. An increase in the renovation rate of existing buildings is the quantitatively measurable outcome.